2006
DOI: 10.1681/asn.2005070742
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic Gluconeogenesis Is Enhanced in Renal Proximal Tubules of Zucker Diabetic Fatty Rats

Abstract: Recent studies indicate that renal gluconeogenesis is substantially stimulated in patients with type 2 diabetes, but the mechanism that is responsible for such stimulation remains unknown. Therefore, this study tested the hypothesis that renal gluconeogenesis is intrinsically elevated in the Zucker diabetic fatty rat, which is considered to be an excellent model of type 2 diabetes. For this, isolated renal proximal tubules from diabetic rats and from their lean nondiabetic littermates were incubated in the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
41
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 47 publications
3
41
1
Order By: Relevance
“…In contrast, we show decreased renal expression of IR protein and phosphorylated IR, the first step in insulin signaling, in alternative rat models of insulin resistance, 6 such as the obese Zucker rats, 6 which have been demonstrated by other investigators 18 to have elevated renal gluconeogenesis. Some of the differences may be due to model/strain differences.…”
contrasting
confidence: 59%
See 1 more Smart Citation
“…In contrast, we show decreased renal expression of IR protein and phosphorylated IR, the first step in insulin signaling, in alternative rat models of insulin resistance, 6 such as the obese Zucker rats, 6 which have been demonstrated by other investigators 18 to have elevated renal gluconeogenesis. Some of the differences may be due to model/strain differences.…”
contrasting
confidence: 59%
“…16,17 Our results concur with the finding of enhanced gluconeogenesis in renal proximal tubules of insulin-resistant Zucker rats. 18 In this regard, we have shown reduced IR in the proximal tubule of insulin-resistant Zucker rats. 6 These data also suggest that transcriptional regulation may be the major mechanism of G6Pase modulators that account for variations observed in G6Pase activity.…”
mentioning
confidence: 70%
“…Recent ex vivo studies showed that renal gluconeogenesis was augmented 38% -66% more in Zucker diabetic fatty rats than in the non-diabetic rats (23) and that CS-917 suppressed gluconeogenesis from lactate in a normal rat perifusion study (6). However, the present study showed that glucose was taken up by the kidney in the overnightfasted diabetic GK rats, and that CS-917 did not decrease glucose release from the kidney in the overnight-fasted state, as described in Figs.…”
Section: Discussionmentioning
confidence: 99%
“…The above data is supported by analysis of gene expression profiles of renal transplants, which revealed reduced FBP-1,6 mRNA level in graft with IF/TA (Scherer et al, 2003). Determination of urinary FBP-1,6 activity was not only used for evaluation of transplanted kidneys, but also to estimate the degree of damage to renal tubules of diabetic patients (Eid et al, 2006), in idiopatic nephrotic syndrome (Kępka et al, 2008) acute pyelonephritis (ZochZwierz et al, 2004), heavy metal (e.g.HgCl 2 ) or, maleic acid intoxication (Kotanko et al, 1984), after trichloroethylene (TCE) administration (Khan et al, 2009). The urinary FBP-1,6 activity significantly increases after nephrotoxic drugs (ifosfamide, cisplatinum) (Pfaller et al, 1994) prednisolone, and azathioprine (Kotanko et al, 1986), cyclosporine, sirolimus and tacrolimus (Klawitter et al,2010).…”
Section: Fbp-16 In Kidney Transplantationmentioning
confidence: 99%